ANALISIS DAMPAK WORK OVERLOAD DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA DENGAN MEMPERHATIKAN MEDIASI WORK STRESS [Studi Pegawai PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Brawijaya] - Indah Sari; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The purpose of this study is to obtain empirical evidence of the effect of Work Overload and the Work Environment on Work Stress and Work Productivity, either directly or through the mediation of Work Stress. This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 64 employees of PT Bank Negara Indonesia (Persero) Tbk Brawijaya Malang Branch Office. Determination of the sample follows the Slovin formula, then the sample is proportional. Empirical evidence shows that both Work Overload and the Work Environment can strongly influence Work Stress and Work Productivity. Likewise, the mediation role of Work Stress is also strong, both for the influence of Work Overload on Work Productivity, as well as for the influence of the Work Environment on Work Productivity of employees of PT Bank Negara Indonesia (Persero) Tbk Brawijaya Malang Branch Office